EXPERIENCE OF SURGICAL TREATMENT AT RECURRENT GASTRIC CANCER - A. V. Chayka; V. M. Khomyakov; L. A. Vashakmadze; V. V. Cheremisov; A. B. Ryabov (Сибирский онкологический журнал)
Introduction. Currently, the only potentially curative treatment for gastric cancer is radical gastrectomy. Even after curative resection, death from gastric cancer is primarily due to recurrence. The purpose of the study was to analyze feasibilities of surgical treatment for recurrent gastric cancer. Methods. From 2000 to 2013, the experience in surgical treatment of 35 patients with recurrent gastric cancer was analyzed. Eight patients underwent surgery for primary gastric cancer in the Thoracic and Abdominal Department of Moscow P.A. Hertsen Cancer Research Institute and 27 patients were operated on in other hospitals including cancer centers. Recurrence from gastric cancer was observed in 6 patients after proximal subtotal gastric resection (PSGR), in 17 patients after distal subtotal gastric resection (DSGR) and in 12 patients after gastrectomy (GE). The median time to recurrence was 22.9 ± 3.4 months. Isolated locoregional recurrence of gastric cancer was detected in 29 patients. Cancer dissemination was diagnosed in 6 patients. Results. Anastomotic recurrence was detected in 22 patients, recurrence within the remnant stomach, in 3 patients, locoregional extra-gastric recurrence in 7 patients and solitary metachronous distant metastases were diagnosed in 3 patients. A total of 33 operations were performed: extirpation of the operated stomach in 12 patients, re-resection of the stomach after DSGR in 2 patients, resection of the esophageal-intestinal anastomosis (after GE) in 8 patients, removal of extra-gastric recurrence in 8 patients and removal of solitary metastases in 2 patients. The complication rate was 45.5 % (15 patients). Grade I complications according to Clavien-Dindo classification were diagnosed in 3 patients, grade II complications in 5 patients, grade IIIA in 2 patients , grade IIIB in 2 patients, grade IV in 2 patients and grade V complications (death from postoperative complications) in 1 patient. The failure of anastomosis sutures was observed in 4 patients, 1 of them died of this complication. Postoperative death rate was 3 %. Long-term treatment outcomes were observed in 32 patients. In patients who underwent surgery, the 1-, 3and 5-year survival rates were 44, 25 and 2.8 %, respectively (р = 0.08). Conclusion. Surgical intervention has been limited to locoregional recurrent gastric cancer. Results of surgical treatment for locoregional extra-gastric recurrence were no worse than those in the treatment for recurrence in the anastomosis or within the remnant stomach.